Do specialist youth cancer services meet the physical, psychological and social needs of adolescents and young adults? A cross sectional study. (February 2020) - Bradford, Natalie; Walker, Rick; Cashion, Christine; Henney, Rosyln; Yates, Patsy
Abstract : Purpose: To assess unmet information and service needs in adolescent and young adult cancer survivors (15–29 years) who access specialist Youth Cancer Services in Queensland, Australia. Methods: Participants were recruited through Youth Cancer Services across Queensland and completed validated Patient Reported Outcome Measures and Patient Reported Experience Measures to assess unmet needs, symptoms and wellbeing and quality of life (QoL) through an online survey. Analysis included Spearman's correlation and t-tests. Results: The sample (N = 42) was representative in terms of gender, cancer type, location of residence and types of treatment. Total QoL varied substantially within the sample, and 56% of total scores were lower than population norms. QoL was inversely correlated with unmet needs (r = −0.64, p=<0.001). There were no explanatory variables identified associated with higher or lower needs or QoL. Young people reported high needs regarding information and support at diagnosis, and for managing side effects and decision making. Most (61–82%) reported these needs were met. At cancer treatment centres, 42% of young people perceived needs were not met regarding talking to other young people, having access to leisure spaces and relevant supportive information. Participants reported low symptom burden and worry about the future but were concerned about their ability to connect with peers and participate in activities. Conclusions: While service and information needs are generally met, young people with cancer who reported higher needs also report substantially lower QoL compared to population norms. Addressing these needs may improve QoL. A continued focus on providing support and services to this population is warranted. Highlights: Around the world, specialist cancer services have been developed to address the specific needs of young people and reduce negative effects of cancer during adolescence and young adulthood. To date there has been little formal evaluation of how these services are meeting the needs of young people with cancer. This manuscript addresses this gap and identifies while many needs are met, young people require more information about after treatment. Addressing the unmet needs of young people may improve their quality of life.